Preventing Peritoneal Dialysis-Associated Fibrosis by Therapeutic Blunting of Peritoneal Toll-Like Receptor Activity - Raby, Anne-Catherine; Labéta, Mario O. (Frontiers in Physiology, 2018)
Peritoneal dialysis (PD) is an essential daily life-saving treatment for end-stage renal failure. A major factor limiting PD therapy remains peritoneal inflammation, which leads to peritoneal membrane failure as a result of progressive fibrosis. Peritoneal infections, with the concomitant acute inflammatory response and membrane fibrosis development, worsen PD patient outcomes. Patients who remain infection-free, however, also show evidence of inflammation-induced membrane damage and fibrosis, leading to PD cessation. In this case, uraemia, prolonged exposure to bio-incompatible PD solutions and surgical catheter insertion have been reported to induce sterile peritoneal inflammation and fibrosis as a result of cellular stress or tissue injury. Attempts to reduce inflammation (either infection-induced or sterile) and, thus, minimise fibrosis development in PD have been hampered because the immunological mechanisms underlying this PD-associated pathology remain to be fully defined. Toll-like receptors (TLRs) are central to mediating inflammatory responses by recognising a wide variety of microorganisms as well as endogenous components released following cellular stress or generated as a consequence of extracellular matrix degradation during tissue injury. Given the close link between inflammation and fibrosis, recent investigations have evaluated the role that TLRs play in infection-induced and sterile peritoneal fibrosis development during PD. Here, we review the findings and discuss the therapeutic potential of blunting peritoneal TLR activity to prevent PD-associated peritoneal fibrosis by using a TLR modulator, the soluble form of TLR2.